2021
DOI: 10.1002/tpg2.20162
|View full text |Cite
|
Sign up to set email alerts
|

Single‐nucleotide mosaicism in citrus: Estimations of somatic mutation rates and total number of variants

Abstract: Most of the hundreds of citrus varieties are derived from spontaneous mutations. We characterized the dynamics of single‐nucleotide mosaicism in a 36‐yr‐old clementine (Citrus ×clementina hort. ex Tanaka) tree, a commercial citrus whose vegetative behavior is known in detail. Whole‐genome sequencing identified 73 reliable somatic mutations, 48% of which were transitions from G/C to A/T, suggesting ultraviolet (UV) exposure as mutagen. The mutations accumulated in sectorized areas of the tree in a nested hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…Conversely, the shape of a phylogeny may enable to infer the dynamics of stem cell lineages that determines the heterogeneity within a SAM. Empirical studies have, in fact, reported both concordance and discrepancies between phylogenetic and physical shapes (Zahrdadníková et al, 2020; Perez-Roman et al, 2021; Satake et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, the shape of a phylogeny may enable to infer the dynamics of stem cell lineages that determines the heterogeneity within a SAM. Empirical studies have, in fact, reported both concordance and discrepancies between phylogenetic and physical shapes (Zahrdadníková et al, 2020; Perez-Roman et al, 2021; Satake et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of genetic variation within an individual has been reported in numerous tree species (Schmid-Siegert et al, 2017;Plomion et al, 2018;Wang et al, 2019;Hanlon et al, 2019;Orr et al, 2020;Hofmeister et al, 2020;Perez-Roman et al, 2021;Duan et al, 2022;Satake et al, 2023). Somatic mutations accumulated as trees age (Satake et al 2023) and were distributed following the branching architecture of a tree (Schmid-Siegert et al, 2017), and the phylogeny of somatic mutations in a single tree showed the same topology as the physical shape of a tree (Perez-Roman et al, 2021;Satake et al 2023). Genetic variation seemingly presented not only among branches but also among cells in a shoot apical meristem (hereafter SAM) of a single branch (Zahrdadníková et al, 2020;Duan et al, 2022;Schmitt et al, 2022).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…3). Since no empirical studies to date have provided evidence of natural selection against somatic mutations within trees (Orr et al, 2019; Perez-Roman et al, 2021; Duan et al, 2022; Imai et al, 2023), we focused exclusively on the neutral mutations in our model.…”
Section: Modelmentioning
confidence: 99%